Post-harvest cold shock treatment enhanced antioxidant capacity to reduce chilling injury and improves the shelf life of guava (Psidium guajava L.) - Zhang, Yan (Frontiers in Sustainable Food Systems, 2024)
This study investigates the impact of storage temperature and cold shock treatment (CST) on the postharvest quality and shelf life of guava fruits. Guavas were stored at varying temperatures (4°C, 6°C, 8°C, and 10°C) for 25 days to evaluate the incidence of chilling injury (CI) and determine optimal storage conditions. Results indicated that the best storage temperature was 6°C, which effectively maintained fruit quality by inhibiting CI, controlling weight loss, and preserving soluble solid content and soluble sugars. Further analysis on the effect of CST on guavas showed that longer cold shock durations (6, 9, and 12 h) before storage at a constant 4°C improved the storage quality and shelf life significantly by decreasing the CI rates, reducing weight loss, maintaining firmness, and improving the fruit’s nutritional quality. Notably, a 12-h CST yielded the best outcomes, evidenced by the lowest malondialdehyde (MDA) content and the highest increases in proline and soluble protein content - biomarkers of enhanced cold tolerance and reduced CI. Additionally, CST was found to modulate the reactive oxygen species (ROS) metabolism, increasing the activity levels of key antioxidant enzymes such as superoxide dismutase (SOD), peroxidase (POD), catalase (CAT), and ascorbate peroxidase (APX), alongside higher contents of ascorbic acid. The study identified a correlation between the length of cold shock and improved antioxidant capacity, crucial for extending guava’s shelf life and preserving quality during cold storage. These findings have significant implications for the postharvest management of guava, recommending 6°C storage and 12-h CST as effective strategies for extending shelf life and ensuring quality in cold storage settings.